2018
DOI: 10.29312/remexca.v5i4.925
|View full text |Cite
|
Sign up to set email alerts
|

Efecto a corto plazo de la fertilización de sitio específico en mangos ‘Kent’ y ‘Tommy Atkins’ cultivados sin riego

Abstract: En el estado de Nayarit, México, no se han realizado ensayos sistemáticos de fertilización en mango. Esta investigación tuvo el objetivo de evaluar el efecto a corto plazo (2010- 2012) de la fertilización de sitio específico (FSE) sobre el crecimiento de los árboles, producción y tamaño de fruto en mangos ‘Kent’ y ‘Tommy Atkins’ cultivados sin riego en Nayarit. Para cada cultivar se usaron dos huertos establecidos en suelos de diferente tipo y nivel de fertilidad. Lo tratamientos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…It should be noted that the amount of nutrients removed described in Table 6 is the minimum amount to be restored for each ton of fresh fruit harvested. As for fertilization recommendations other factors should be considered, such as frequency and amount of pruned wood (Cruz-Barrón et al, 2014), leaf and soil analysis, the nutrient requirement of the tree for a given production target, tree phenology, and the eff iciency and method of applying fertilizers and/or manures, among other factors (Salazar-García et al, 2014).…”
Section: Nutrient Removalmentioning
confidence: 99%
“…It should be noted that the amount of nutrients removed described in Table 6 is the minimum amount to be restored for each ton of fresh fruit harvested. As for fertilization recommendations other factors should be considered, such as frequency and amount of pruned wood (Cruz-Barrón et al, 2014), leaf and soil analysis, the nutrient requirement of the tree for a given production target, tree phenology, and the eff iciency and method of applying fertilizers and/or manures, among other factors (Salazar-García et al, 2014).…”
Section: Nutrient Removalmentioning
confidence: 99%
“…En el estado de Nayarit (México), Salazar-García et al, (2014) desarrollaron una investigación en mango (Mangifera indica L.) en dos variedades "Kent" y "Tommy Atkins" cultivados sin riego, y reportaron que la nutrición potásica puede variar el rendimiento en función a la variedad, ya que para obtener el máximo rendimiento en "Tommy Atkins"…”
Section: Nutrición Potásica En Frutalesunclassified
“…In the state of Nayarit (Mexico), Salazar-García et al, (2014) developed an investigation in mango (Mangifera indica L.) in two varieties "Kent" and "Tommy Atkins" cultivated with no irrigation, and reported that potassium nutrition can vary in function to the variety, since to obtain the maximum yield in "Tommy Atkins" (186.9 Kg tree -1 ) a dose of 455-572 g was necessary, and for "Kent", the maximum yield (138.2 Kg tree -1 ) was obtained with a dose of 259-325 g K 2 O tree -1 , while the control yield was 115.5 Kg tree -1 .…”
Section: Potassium Nutrition In Fruit Treesmentioning
confidence: 99%
“…The site-specif ic fertilization (SSF) approach allows increases in yield and fruit quality and reduces environmental pollution due to excessive application of fertilizers and/or organic materials (Salazar- García, 2002;Salazar-García et al, 2009;Salazar-García et al, 2014). One of the possible causes for the low yield of 'Ataulfo' mango in Nayarit is insuff icient and/or unbalanced orchard fertilization, so the SSF approach can provide signif icant increases in fruit yield and quality on a short-term basis (Salazar- García et al, 2014;García-Martínez et al, 2015). The objective of this research was to evaluate the effect of the SSF approach on fruit yield and size of rainfed 'Ataúlfo' mango in Nayarit, Mexico.…”
Section: Introductionmentioning
confidence: 99%